DESAIN JEMBATAN LEMAH GEMPAL KOTA SEMARANG DENGAN RANGKA BAJA - Shinta Sukian; Indrastono Dwi Atmanto; Ilham Nurhuda (Jurnal Karya Teknik Sipil, 2013)
The construction of Lemah Gempal Bridge in Semarang is aimed at providing alternative access to reduce traffic congestion around Siliwangi street and Kaligarang street. The construction of this road is to connect lemah Gempal and Simongan area in west semarang. The writer desained Lemah Gempal steel truss  bridge which spans 80 meters length accross banjir kanal river. This bridge consists of two spans, each span has 40 meters length. The bridge has  one pillar and two abutment. The  width of the bridge is 9 meters and divided into 2 lane. Each lanes  is 3,5 meters width. There are trotoars of I meter length on each side of  the lane.